Developing Interactive Learning Media through Canva Website and Quizizz Mastery Peak Integration to Enhance Problem-Solving Skills - Margareta, Diswa; Karimah, Sayyidatul (Kognitif: Jurnal Riset HOTS Pendidikan Matematika, 2025)
This study addresses the low motivation and limited problem-solving ability of students in mathematics, as well as the insufficient use of interactive digital learning media in schools. Preliminary observations of grade X students at SMA Negeri 2 Batang indicated low enthusiasm toward conventional mathematics instruction with minimal interactivity. To overcome this challenge, innovative media were developed using Canva Website integrated with the Quizizz Mastery Peak platform through a gamification approach. The development process employed the ADDIE model, which consists of five systematic stages: analysis, design, development, implementation, and evaluation. Data were collected through observations, interviews, needs questionnaires, expert validation, and student responses. Eight experts, including lecturers and mathematics teachers, validated the media, while practicality testing involved 27 grade X.2 students. The results indicated that the media met the criteria of validity and was rated as highly practical by students. Integration of Canva Website and Quizizz Mastery Peak has the potential to foster student engagement, interactivity, and active participation in mathematics learning. Nevertheless, further experimental or quasi-experimental research is required to rigorously evaluate its effectiveness in significantly improving mathematical problem-solving skills.